Tinjauan literatur: Anak hiperaktif dalam perspektif abnormal dan Islam - Rahmania, Chafidhotur; Anwar, Maulida Miftahul; Jamaluddin, Muhammad (Maliki Interdisciplinary Journal, 2024)
A review of the literature on hyperactive children from an abnormal and Islamic perspective illustrates the importance of understanding this condition from a psychological and spiritual perspective. Clinically, hyperactive children often experience difficulties in concentration, impulsivity, and hyperactivity, which can affect their social interactions and academic performance. Many psychological studies have explored various factors that cause hyperactivity, including genetics, environment, and neurobiological factors. On the other hand, the Islamic perspective emphasizes the importance of a holistic approach to mental and spiritual health. In Islam, there is an understanding of the complexity of humans as spiritual and physical creatures, and the importance of balancing between the two. In dealing with hyperactive children, a holistic approach based on Islamic values ​​can provide a broader and deeper view. This includes not only medical and psychological interventions, but also spiritual aspects such as prayer, patience, and increased awareness of spiritual duties. By combining psychological and spiritual understanding, a comprehensive approach can be created to help hyperactive children and their families manage this condition more effectively.